Laser powder bed fusion of boron nitride nanotubes (BNNTs) and multi-wall carbon nanotubes (MWCNTs) functionalised Polyamide-12 nanocomposites with improved powder reusability - Ollekkatt Sivadas, Binsha (2025)
Polymer Laser Powder Bed Fusion (P-LPBF) is a widely used Additive Manufacturing (AM) technique that is known to be one of the cheapest AM methods for batch fabrication. The limited material palette is one of the drawbacks of P-LPBF. Most commercially available PA12 powders for P-LPBF have poor reusability (~50%) of unfused powder. The poor reusability makes it prohibitively expensive to develop Polymer Nanocomposite (PNC) powders, especially when using costly nanomaterials. Hence, no study has explored functionalisation with exotic nanomaterials such as hexagonal Boron Nitride Nanotubes (BNNTs) that cost ~$600 per gram. Thus, choosing a highly reusable polymer matrix is key to reducing waste, cost and carbon footprint.